Measurement of noise source impedance of SMPS using two current probes method - Yang, Lin (2008)
This thesis presents a novel two current probes methods that allow accurate and reliable measurement of noise source impedance of SMPS. Based on the developed noise source model, a systematic approach to design a power filter design for a specific SMPS is now possible.